Penerapan Strategi Pembelajaran PDEODE untuk Meningkatkan Keterampilan Berpikir Kritis dan Hasil Belajar Peserta Didik Kelas VII SMPN 14 Kendari pada Materi Pokok Kalor dan Perpindahnnya - Supraningsi A.B, Putri; Anas, Muhammad; M, Hunaidah (Jurnal Penelitian Pendidikan Fisika, 2020)
This study is motivated by the low critical thinking skills and learning outcomes possessed by the students of VII grade of SMPN 14 Kendari. This study aims to determine the enhancement in critical thinking skills and learning outcomes on the subject Matter of Heat and Its Transfer. The population of this study were all students of VII grade of SMPN 14 Kendari who were registered in the odd semester in 2019/2020 school year, with total 204 students. The sample of this research was group VII3 with total 41 students as the experimental group and group VII4 with total 41 students as the control group who were taken by using random sampling techniques. The research data were analysed by using descriptive and inferential statistics. Research results show: 1) There is no significant difference between the pre-test average scores of students critical thinking skills in the experimental group and the control group; 2) There is no significant difference between the pre-test average scores of the experimental group students and the control group; 3) The post-test average score of students from critical thinking skills in the experimental group was significantly higher than in the control group; 4) The post-test average score of the experimental group students was significantly higher than in the control group; 5) The average value of N-gain critical thinking skills of students in the experimental group was significantly higher than the control group; 6) ) The average value of N-gain learning outcomes of students in the experimental group was significantly higher than the control group.